IMPLEMENTING SONG AS MEDIA FOR TEACHING VOCABULARY - Rizki Januar Herliawan; Dasep Suprijadi (IKIP Siliwangi, 2024)
The covid-19 pandemic has affected the educational field so that the government have been made a regulation for schools in Indonesia to carried out online teaching-learning. However, English should be learned by the students in this pandemic condition to make the students practice their English. Due to the online learning, the students still found problems and difficulty in implementing songs as the media. This research aims to find out the problems faced during online teaching and learning particularly in vocabulary learning through English songs to the ninth-grade students at one of Junior High Schools in Bandung. The respondents were the 9 students of ninth-grade students at one of Junior High Schools in Bandung. The data was conducted by observation and test. Based on the result it can be concluded that online vocabulary learning has some obstacles faced by the teacher and students such as internet connection 13%, managing time 10%, devices 10%, technology mastery 4%, noises 10%. Moreover, these obstacles have been impacted the students that the students difficult to do and collect assignments 10%, the students cannot fully understand the materials 8%, the students became passive 8%, students feel bored 8%, students cannot do as teamwork 8%, and the students cannot follow the learning process 6%.